2015
DOI: 10.1371/journal.pone.0132032
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Salmonella Expressing Burkholderia mallei LPS O Antigen Provides Protection in a Murine Model of Melioidosis and Glanders

Abstract: Burkholderia pseudomallei and Burkholderia mallei are the etiologic agents of melioidosis and glanders, respectively. These bacteria are highly infectious via the respiratory route and can cause severe and often fatal diseases in humans and animals. Both species are considered potential agents of biological warfare; they are classified as category B priority pathogens. Currently there are no human or veterinary vaccines available against these pathogens. Consequently efforts are directed towards the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 90 publications
2
15
0
Order By: Relevance
“…All three of the recombinant vaccine strains stimulated more serum IgG2a (characteristic of a Th1-type response) than IgG1 (characteristic of a Th2-type response) against the heterologous LPS post-second immunization, indicating a biased Th1-type immune response. This finding was consistent with a number of studies in which recombinant antigens expressed in oral, attenuated Salmonella vaccines induced a predominately Th1 response, as did the vector itself (VanCott et al, 1996 ; Pathangey et al, 2009 ; Moustafa et al, 2015 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All three of the recombinant vaccine strains stimulated more serum IgG2a (characteristic of a Th1-type response) than IgG1 (characteristic of a Th2-type response) against the heterologous LPS post-second immunization, indicating a biased Th1-type immune response. This finding was consistent with a number of studies in which recombinant antigens expressed in oral, attenuated Salmonella vaccines induced a predominately Th1 response, as did the vector itself (VanCott et al, 1996 ; Pathangey et al, 2009 ; Moustafa et al, 2015 ).…”
Section: Discussionsupporting
confidence: 88%
“…As an ideal vaccine vector, live attenuated Salmonella vaccines have been utilized to deliver O-antigens from other pathogenic bacteria, such as Shigella sonnei (Dharmasena et al, 2013 ) and Burkholderia mallei (Moustafa et al, 2015 ), exhibiting protection against lethal challenge. However, a Salmonella vaccine strain expressing Pseudomonas aeruginosa O-antigen exhibits only partial protection against lethal challenge (Bridge et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional live attenuated vaccine platforms that protect against wild-type Bp infection include Bt-or Salmonella sp.-based vaccines [74] [75]. Burkholderia thailandensis is a less pathogenic species closely-related to Bp and Bm and therefore represents both an excellent surrogate model and a potential vaccine candidate for biothreat Burkholderia sp.…”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%
“…Additional vaccine approaches make use of the similarity between the Bt, Bp, and Bm OPS, such as a Salmonella enterica serovar Typhimurium SL3261 aroA mutant constructed to express the Bm OPS [75]. The protective efficacy of this vaccine construct was assessed in a murine lethal intranasal Bt model that mimics melioidosis and glanders, and it was shown that intranasal vaccination provided significant protection and sterile immunity at 72 h following challenge with 5LD 50 of Bt, though long-term bacterial burdens were not assessed [75].…”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%
“…For Burkholderia subunit vaccines, these include lipopolysaccharides (LPS) and outer membrane proteins and vesicles (OMP and OMV, respectively). LPS have shown to play an important role in the pathogenesis of Burkholderia infection and a number of LPS molecules have been identified in B. pseudomallei and B. mallei , which are therefore, a likely target for subunit vaccines [45]. As a potent inducer of host immune responses, LPS O-antigen has been shown to provide epitopes for the development of antigen-specific antibodies, and the lipid A region is a potent agonist for Toll-like receptors (TLRs) [46].…”
Section: Subunit Vaccinesmentioning
confidence: 99%